Frequency of Prolonged QT Interval in Obese, Hypertensive and Diabetic Patients - RASHID IQBAL, MUNIB ULLAH MIRZA, MUHAMMA, KHURRAM SALEEM, KHALID MAHMUD KHAN (Journal of Fatima Jinnah Medical University, 2018)
Objective: Examine the effect of obesity, hypertension and diabetes on QTc interval. Materials and methods: cross-sectional study, department of Medicine, Mayo hospital Lahore.50 unselected patients of obesity, diabetes and hypertension .QTc was calculated using Bazett’s equation. Results: A relevant association between prolonged QTc and age (P=0.85), duration of diabetes (P=0.372), duration of hypertension (P=0.213) and BMI (P=0.273) was observed. Out of total 50 patients, 16 males and 34 females with mean duration of diabetes 8.68yrs and 7.42 years, with hypertension of around 3.14years and 4.67 years. It was seen that in class II obesity (BMI >40)QTc interval was increased in a proportionate manner of 495ms. Conclusion: QTc maybe an independent marker for cardiovascular, cerebrovascular and total morbidity and mortality.